Safety and usage of darbepoetin alfa in children with chronic kidney disease: prospective registry study - Schaefer, Franz; Hoppe, Bernd; Jungraithmayr, Therese; Klaus, Günter; Pape, Lars; Farouk, Mourad; Addison, Janet; Manamley, Nick; Vondrak, Karel (Pediatric nephrology, 2016)
Limited prospective data are available on the long-term safety of darbepoetin alfa (DA) for treating anemia in children with chronic kidney disease (CKD).
Published online: 19 October 2015
Gesehen am 12.05.2020